Psychedelics, epilepsy, and seizures: a review - Freidel, Ninon; Kreuder, Liliane; Rabinovitch, Brenden Samuel; Chen, Frank Yizhao; Huang, Ryan S. T.; Lewis, Evan Cole (Frontiers in Pharmacology, 2024)
Psychedelic compounds have been utilized by humans for centuries for medicinal, religious, and tribal purposes. Clinical trial data starting from the early 2000s and continuing today indicates that psychedelics are a clinically efficacious treatment for a variety of neurological and psychiatric disorders. However, all clinical trials examining these substances have excluded any individual with a past or current history of seizures, leaving a large cohort of epilepsy and non-epilepsy chronic seizure disorder patients without anywhere to turn for psychedelic-assisted therapy. These exclusions were made despite any significant evidence that clinically supervised psychedelic use causes or exacerbates seizures in this population. To date, no clinical trial or preclinical seizure model has demonstrated that psychedelics induce seizures. This review highlights several cases of individuals experiencing seizures or seizure remission following psychedelic use, with the overall trend being that psychedelics are safe for use in a controlled, supervised clinical setting. We also suggest future research directions for this field.